Implementation of Primary Team Professional Nursing Practice Methods In Hospital: A Systematic Review - Merbawani, Raras; Munfadlila, Asef Wildan (Journal Of Nursing Practice, 2021)
Background: The hospital is a health service organization that provides comprehensive health services that achieve promotive, preventive, curative and rehabilitative aspects for the community. The application of the Professional Nursing Practice Method (MPKP) can illustrate the efforts of various countries to improve the quality of nursing care and the working environment of nurses in hospitals.Purpose: The purpose of this study was to determine the application of MPKP in hospitals.Methods: This research design uses a literature review, which is a series of studies relating to the method of collecting library data, or research whose research objects are explored through various library information (books, encyclopedias, scientific journals, newspapers, magazines, and documents) from several journals that have been researched by previous researchers who have been screened with inclusion and exclusion criteria using several databases namely google shoolar, lib UI, and SINTA which will be used as a literature review in this study. There are 155 journals according to keywords which are screened into 10 journals according to the theme and analyzed which examines the application of the Professional Nursing Practice Method (MPKP).  Results: The results showed that the implementation of MPKP was in the good category and was more dominant, namely 40% in the nursing care system. In the application of the maximum Professional Nursing Practice Method (MPKP) and good categories, nurses have to make professional values, professional relationships, management approaches, nursing care systems, and reward compensation systems according to nursing standards by looking at performance and determining the appropriate MPKP model.  Conclusion: The better the implementation of the Professional Nursing Practice Method (MPKP) is carried out, the better the services provided by the hospital to patients